Leveraging Large Language Models (LLM) for the Plastic Surgery Resident Training: Do They Have a Role? - Devi Prasad Mohapatra; Friji Meethale Thiruvoth; Satyaswarup Tripathy; Sheeja Rajan; Madhubari Vathulya; Palukuri Lakshmi; Veena K. Singh; Ansar Ul Haq (Indian Journal of Plastic Surgery)
Introduction Large language models (LLMs) are designed for recognizing, summarizing, translating, predicting, and generating text-based content from knowledge gained from extensive data sets. ChatGPT4 (Generative Pre-trained Transformer 4) (OpenAI, San Francisco, California, United States) is a transformer-based LLM model pretrained on public data as well as data obtained from third-party sources using deep learning techniques of fine tuning and reinforcement learning from human feedback to predict the next text. We wanted to explore the role of LLM as a teaching assistant (TA) in plastic surgery.